PH‐dependence of single‐protein adsorption and diffusion at a liquid chromatographic interface. Issue 4 (20th October 2015) - Kisley, Lydia; Poongavanam, Mohan‐Vivekanandan; Kourentzi, Katerina; Willson, Richard C.; Landes, Christy F.
Abstract : pH is a common mobile phase variable used to control protein separations due to the tunable nature of amino acid and adsorbent charge. Like other column variables such as column density and ligand loading density, pH is usually optimized empirically. Single‐molecule spectroscopy extracts molecular‐scale data to provide a framework for mechanistic optimization of pH. The adsorption and diffusion of a model globular protein, α‐lactalbumin, was studied by single‐molecule microscopy at a silica–aqueous interface analogous to aqueous normal phase and hydrophilic interaction chromatography and capillary electrophoresis interfaces at varied pH. Electrostatic repulsion resulting in free diffusion was observed at pH above the isoelectric point of the protein. In contrast, at low pH strong adsorption and surface diffusion with either no ( D ∼ 0.01 μm 2 /s) or translational ( D ∼ 0.3 μm 2 /s) motion was observed where the protein likely interacted with the surface through electrostatic, hydrophobic, and hydrogen bonding forces. The fraction of proteins immobilized could be increased by lowering the pH. These results show that retention of proteins at the silica interface cannot be viewed solely as an adsorption/desorption process and that the type of surface diffusion, which ultimately leads to ensemble chromatographic separations, can be controlled by tuning long‐range electrostatic and short‐range hydrophobic and hydrogen bonding forces with pH.